How do I solve this precalc problem?

Mathematics
Tutor: None Selected Time limit: 1 Day

sin2a - cosa = 0. Find all solutions of the equation in the interval [0, 2 π)

Jun 4th, 2015

Thank you for the opportunity to help you with your question!

Ok, first we use this trigonometric identity (double angle formula for the sine function) which is:

sin(2a) = 2sin(a)cos(a)

So we enter it into the original expression resulting:

sin(2a) -cos(a) = 0  ----------->  2sin(a)cos(a) - cos(a) = 0

So here we can see that we have a common factor which is the cos(a) since we have it twice in our expression: 

2sin(a)cos(a) - cos(a) = 0

Then we factor cos(a) out from the whole expression like this:

cos(a)(2sin(a) - 1) = 0

After this, we equal each factor to zero and solve for a. So we would have the following:

cos(a) = 0     and     2sin(a) - 1 = 0

So we solve the first equation for a by taking the inverse function from both sides (which is arccos).

cos(a) = 0  ----------->  arccos(cos(a)) = arccos(0)  ------------> a = arccos(0)

In order to get the arccos(0) we need to find the angles or radians at which the cosine function is equal to zero.

So let's remember the cosine function is zero at the the odd multiples of Pi/2 which are: Pi/2, 3Pi/2, 5Pi/2, 7Pi/2...

Since it says that we just consider the solutions between the interval [0 , 2Pi) then we just consider

a = Pi/2 and a = 3Pi/2

Now we solve the other equation which is: 2sin(a) - 1 = 0. So first, we add 1 from both sides like this:

2sin(a) - 1 = 0  ------------>  2sin(a) - 1 + 1 = 0 + 1  --------------->  2sin(a) = 1

Then we divide by 2 from both sides:

2sin(a) = 1  --------------->  2sin(a)/2 = 1/2   --------------> sin(a) = 1/2

Finally, we take the inverse of the sine function from both sides (the arcsin):

sin(a) = 1/2  --------------->  arcsin(sin(a)) = arcsin(1/2)  -----------------> a = arcsin(1/2)

So in order to find the arcsin(1/2) we need to find the angles or radians at which the sine function is equal to 1/2.

Then we have:  a = Pi/6. In order to get the other solution we just subtract Pi from the first solution. So we have:

a = Pi - Pi/6 = Pi(1 - 1/6) = Pi(6/6 - 1/6) = Pi(5/6) = 5Pi/6.

So finally, the solutions are: a = Pi/6 , a = 5Pi/6 , a = Pi/2 , a = 3Pi/2


Please let me know if you need any clarification. I'm always happy to answer your questions.
Jun 4th, 2015

Are you studying on the go? Check out our FREE app and post questions on the fly!
Download on the
App Store
...
Jun 4th, 2015
...
Jun 4th, 2015
Dec 6th, 2016
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer